New molecular mechanisms to explain the neuroprotective effects of insulin-like growth factor II in a cellular model of Parkinson's disease - Romero-Zerbo, Silvana Yanina; Valverde, Nadia; Claros-Gil, Silvia; Zamorano-González, Pablo; Boraldi, Federica; Lofaro, Francesco-Demetrio; Lara, Estrella; Pavía-Molina, José; García-Fernández, María Inmaculada; Gago-Calderón, Belén; Martín-Montañez, Elisa (Elsevier, 2024)
Introduction One of the hallmarks of Parkinsońs Disease (PD) is oxidative distress, leading to mitochondrial dysfunction and neurodegeneration. Insulin-like growth factor II (IGF-II) has been proven to have antioxidant and neuroprotective effects in some neurodegenerative diseases, including PD. Consequently, there is growing interest in understanding the different mechanisms involved in the neuroprotective effect of this hormone. Objectives To clarify the mechanism of action of IGF-II involved in the protective effect of this hormone. Methods The present study was carried out on a cellular model PD based on the incubation of dopaminergic cells (SN4741) in a culture with the toxic 1-methyl-4-phenylpyridinium (MPP+), in the presence of IGF-II. This model undertakes proteomic analyses in order to understand which molecular cell pathways might be involved in the neuroprotective effect of IGF-II. The most important proteins found in the proteomic study were tested by Western blot, colorimetric enzymatic activity assay and immunocytochemistry. Along with the proteomic study, mitochondrial morphology and function were also studied by transmission electron microscopy and oxygen consumption rate. The cell cycle was also analysed using 7AAd/BrdU staining, and flow cytometry. Results The results obtained indicate that MPP+, MPP++IGF-II treatment and IGF-II, when compared to control, modified the expression of 197, 246 proteins and 207 respectively. Some of these proteins were found to be involved in mitochondrial structure and function, and cell cycle regulation. Including IGF-II in the incubation medium prevents the cell damage induced by MPP+, recovering mitochondrial function and cell cycle dysregulation, and thereby decreasing apoptosis.
Keywords: Parkinson, Enfermedad de; Mitocondrias; Ciclo celular; Parkinson´ s disease; IGF-II; Neuroprotection; Mitochondria; Cell cycle